Screening of paprika (Capsicum annuum L.) varieties resistant to NaCl salt stress - Massimi, Mohunnad; Radocz, Laszlo (Acta Agraria Debreceniensis, 2022)
Salinity stress is one of the environmental factors that negatively affect the growth and production of pepper plants. The 100 seeds' weight was measured. The total fresh weight of five seedlings and the growth rate of one seedling of three paprika varieties were also measured under the influence of NaCl at a salinity level threshold of (3 dS m‑1). The proportion of tissue water content in three pepper cultivars was measured according to a mathematical formula at the end of the experiment. In terms of seed weight, the (Carma) cultivar outperformed other types greatly. Except for the superiority of both (Carma, and Bobita F1) over (Fokusz) variety in total fresh seedlings weight under sodium chloride as abiotic stress, there are no significant differences in the total seedlings' dry weight and the rate of seedling growth. The non-drought-resistant type (Bobita F1) loses water the fastest, at 89.61%, compared to drought-tolerant kinds, which lose water at a slower rate (Carma, and Fokusz). The results demonstrate the (Carma) variety's numerical vigor, particularly in the growth rate. More testing is needed to determine the selection of varieties that are resistant to abiotic and biotic stresses.